Understanding specific learning difficulties - Prior, Margot R. (Psychology Press, 1996)
Introduction. Reading and spelling problems. Problems with mathematics. Diagnosis and assessment. Neuropsychology and its uses in understanding learning difficulties. The relationship between behaviour problems and learning difficulties. Intervention. Remedial techniques and resources...